Role of Magnesium Sulphate for Prevention of Postoperative Atrial Fibrillation in Patients Undergoing Open Heart Bypass (CABG) Surgery - Ali, Ashia; Hassan, Md Kamrul; Nuruzzaman, Mostofa; zzaman, Sumsu; Rahman, Mostafizur; Hoque, Rezwanul (University Heart Journal, 2012)
To assess the role of magnesium sulphate infusion after coronary artery bypass graft (CABG) surgery in preventing atrial arrhythmias that may occur following CABG operation. Cardiac anaesthesia wing of Bangabandhu Sheik Mujib Medical University, Dhaka from 2007 to 2009. Design: Prospective randomized non blined. All patients under going primary CABG surgery and having sinus rhythm before surgery were alternatively randomized into the study or control group. Patient with history of Atrial Fibrillation (AF), Left Atrial (LA) dysfunction, renal-impairment and implanted pace maker were excluded from the study. The patients in the study group received 10 mmol of magnesium (2.47gm) in 10 ml saline intravenously over 10 min after termination of Cardio Pulmonary Bypass (CPB). The end point was development 0f AF for 10 min or if an episode of AF had to be treated because of symptoms. A total of 60 patients were included in the study 30 in each group. The incident of AF was 14% in patients who received single dose of magnesium. The patients without magnesium had an AF incidence of 20% (p=0.353) not significant. Single dose magnesium infusion does not prevent AF statistically, but the haemodynamic parameters in patients receiving magnesium were more stable during the whole period of observation. DOI: http://dx.doi.org/10.3329/uhj.v8i1.11661 University Heart Journal Vol. 8, No. 1, January 2012